Youth involvement and volunteerism: MEKAR project at Selama Malaysia - Nur Ziella Isshamila,; Asma Mat,; Diana Wulandari, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Youth involvement and volunteerism have emerged as crucial components in addressing contemporary societal challenges. This article aims to explore the significance of youth engagement in volunteer activities, its impact on personal development, and community empowerment, and the broader implications for creating positive social change. This article also delves into the various forms of youth volunteerism, ranging from local community projects to global humanitarian efforts, highlighting the diverse avenues through which young people contribute to society. The article also examines the benefits of youth involvement in volunteerism, such as skill enhancement, increased civic awareness, and the cultivation of empathy and leadership qualities. By analyzing existing literature and case studies (MEKAR), this article underscores the potential of youth involvement in volunteerism to foster social innovation and positive transformation. The result emphasizes the reciprocal relationship between youth and the communities they serve, wherein volunteerism not only addresses community needs but also nurtures a sense of belonging and purpose among young participants. Hence, this article sheds light on the multifaceted aspects of youth involvement and volunteerism, portraying it as a dynamic force for social progress.